The local meteoric water line in the Pampean Plain of Córdoba, Argentina - Cabrera, Adriana (2019)
Stable isotopes are very useful to trace groundwater from their recharge origin as precipitation. This is due to the conservation of the meteoric signal during its subsurface flow. Thus, is very important to have a local meteoric line (LML) in every world region to more accurately adjust the interpretations of hydrological relationships and processes like recharge areas, evaporation, water mixtures and probable isotopic exchanges with rocks and sediments. The objective of this work is to analyze the isotopic composition of precipitations in the dry sub-humid sector of the Pampa plain of Córdoba, its connection with the meteorological conditions and the temporal variations to improve the comprehension of the input function to the regional hydrological systems. The isotopic values were evaluated and the arithmetic and weighted averages were calculated. The local meteoric line was defined using a least square regression. Precipitation in the South of Cordoba province is characterized by average values of δ18O and δ2H of -4.7 ‰ and -23.5 ‰. The obtained local meteoric line is represented by the equation δ2H = 8.3 δ18O + 15.2 ‰ considered representative of the sub-humid-dry sector of the Pampean plain. From September to April, in which the most important precipitations and the highest temperatures occur, is where the most enriched precipitation falls and with the highest deuterium excess values. From May to August, the period in which the lowest precipitation amounts and the lowest temperatures are recorded, the precipitation is more isotopically impoverished showing the lowest “d” values. The observed variations in “d” reveal different origins of the air masses that originate the precipitations, mainly recycled steam linked to the jet stream in low layers, and also the influence during some months of the ENSO phenomenon and the ITZC variation. For the hydrological studies in the Pampean plain of the province of Cordoba, this local meteoric line is a very important basis to compare with the isotope composition of the different hydrological systems for the understanding of the recharge areas, water mixtures, the hydrodynamic and even chemical relationships in the different hydrological environments.